2018
DOI: 10.1111/php.13060
|View full text |Cite
|
Sign up to set email alerts
|

Disinfect Porphyromonas gingivalis Biofilm on Titanium Surface with Combined Application of Chlorhexidine and Antimicrobial Photodynamic Therapy

Abstract: Various antimicrobial modalities have been proposed to treat peri‐implantitis but resulted in limited outcomes. The aim of this in vitro study was to evaluate the disinfection efficacy of combined application of chlorhexidine digluconate (CHX) and antimicrobial photodynamic therapy (aPDT) of titanium surfaces previously contaminated with Porphyromonas gingivalis biofilm. P. gingivalis biofilms were grown on 32 polished and 32 sandblasted large‐grit acid‐etched (SLA) titanium surfaces. Titanium disks were alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
2
12
0
4
Order By: Relevance
“…Chlorhexidine immersion also showed modest decontamination rates, being similar or slightly superior to other studies 20,29,31,32 . As observed by Cai et al., 32 no difference was noted in its decontamination potential on smooth or rough surfaces. Although ineffective, the results obtained with the use of chlorhexidine in our study may have been favored because it was used as a more concentrated solution.…”
Section: Discussionsupporting
confidence: 80%
“…Chlorhexidine immersion also showed modest decontamination rates, being similar or slightly superior to other studies 20,29,31,32 . As observed by Cai et al., 32 no difference was noted in its decontamination potential on smooth or rough surfaces. Although ineffective, the results obtained with the use of chlorhexidine in our study may have been favored because it was used as a more concentrated solution.…”
Section: Discussionsupporting
confidence: 80%
“…The combination of CHX plus aPDT has been tried against other microorganisms such as Porphyromonas gingivalis biofilm on a titanium surface in a dental framework. The application of CHX and subsequent aPDT using toluidine blue O was shown to be an efficient method to reduce P. gingivalis in titanium surfaces [ 39 ]. Regarding other studies of antimicrobials plus aPDT against Candida spp., Giroldo et al demonstrated that yeasts, both in suspension and in biofilms, were much more susceptible to antifungal treatments after MB-aPDT, explained by the increase of membrane permeability caused by aPDT [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the Three Rs principles ( Replacement , Reduction and Refinement ), the initial evaluation of implant decontamination should be performed in vitro . 29 Although it is not always possible to completely replace animal models with in vitro techniques, it is advisable that non-animal experiments are carried out to collect initial data and thus refine the design of subsequent preclinical studies. In a review of in vitro studies focused on the treatment of peri-implantitis, Benli et al 30 concluded that titanium discs, sectioned implants and titanium surfaces were commonly used as test samples.…”
Section: Discussionmentioning
confidence: 99%